A Novel Technique Using Fluorescent Ureteral Catheter and Flexible Ureteroscope for Safe Laparoscopic Fenestration of Lymphocele after Kidney Transplantation. (7th February 2022) - Sekito, Takanori; Araki, Motoo; Wada, Koichiro; Yoshinaga, Kasumi; Maruyama, Yuki; Sadahira, Takuya; Katayama, Satoshi; Iwata, Takehiro; Nishimura, Shingo; Sako, Tomoko; Edamura, Kohei; Kobayashi, Yasuyuki; et al.
Abstract : Laparoscopic fenestration of a postrenal transplant lymphocele is associated with a risk of renal hilar vessel and ureteral injury. Consequently, determination of the incision line is difficult. We describe a case of a 73-year-old man with postrenal transplant lymphocele who underwent a laparoscopic fenestration. We report a surgical video containing a new technique of laparoscopic fenestration using a fluorescent ureteral catheter in combination with a flexible ureteroscope. The combination of a fluorescent ureteral catheter and flexible ureteroscope during surgery enabled us to determine the incision line safely and accurately. Intraoperative real-time visualization of the lymphocele and ureter using a fluorescent ureteral catheter and a flexible ureteroscope is safer than conventional methods for laparoscopic fenestration. To the best of our knowledge, this is the first report of this novel technique.